Integrated Internet Marketing Program for B2B Sector Company - Olesya V. IVANCHENKO; Elena V. BARAULYA; Yulia N. LOBAS (Communications of International Proceedings, 2021)
The article discusses the development of an integrated Internet marketing program in the activities of a B2B company within the framework of the simultaneous use and interconnection of several online communication channels with target consumers to achieve the company's marketing goals. The actual tools of Internet marketing have been identified, the stages of development of a complex Internet marketing program have been highlighted. Particular attention is paid to a practical approach to the development of an integrated Internet marketing program using the example of a company operating in the B2B market. The conclusion is made that the implementation of the integrated Internet marketing program results in the increased efficiency of the company's activity in the Internet environment.
Keywords: Internet Marketing; Marketing Program; Online Communication Channel; Promotion; Target Consumer; Integrated Internet Marketing.